An investigation of the real effects of government expenditures - Arroyo, Gloria M. (Philippine Review of Economics and Business (formerly The Philippine Review of Business and Economics), 1987)
The paper examines the macroeconomic effects of government expenditures. The possible crowding-out effects of government expenditures on private consumption are investigated under the notion that the possible benefits of government spending, as well as the changes in disposable income due to tax changes are both perceived by people -- a case of two-sided rationality. The discussion takes off from the empirical work of Feldstein in defense of the multiplier effect of government purchases, and that of Kormendi about the crowding-out effect of government expenditures on consumption. The paper then tests the implications of the consolidated approach to modeling consumer behavior developed by Barro and Bailey with Philippine aggregate data. Results show that the various specifications of the consumption function were characterized by significant and large negative effects of government expenditures on private consumption. It is thus concluded that in the Philippines, government expenditures have a strong crowding-out effect on private consumption. This effect tends to dampen rather than raise output and employment.